Experiences and Perceptions on Community Client-Led ART Delivery (CCLADS) Model of Antiretroviral (ART) Delivery: Patients’ and Providers’ Perspectives in South Western Uganda. - Kasande, Meble; Tusimiirwe, Happiness; Taremwa, Michael; Lamulatu, Kabiite; Amanyire, Mark; Nakidde, Gladys; Kabami, Jane (Kabale University, 2024)
Purpose: Community Client-Led ART Delivery groups (CCLADS) were introduced as part of the differentiated service delivery models in 2017 to better serve the growing number of HIV patients and reduce unnecessary burden on the HIV care delivery system. However, there is limited evidence on the exact experiences and perceptions of patients and care providers regarding the CCLADS model of ART delivery. We, therefore, aimed to explore the experiences and perceptions of the CCLADS model from the patient and provider perspectives. Participants and Methods: A descriptive qualitative study was conducted at two ART clinics in Southwestern Uganda. We conducted in-depth interviews (IDI) to get a deeper understanding of the patient and providers’ perspectives regarding the model. Responses from participants were recorded using audio recorders and were translated and transcribed. We used a thematic approach to analyze the data. Results: A total of 20 in-depth interviews were conducted, with providers, CCLAD leaders, and Adults Living with HIV (ALHIV) to assess the experiences and perceptions of participation among People Living with HIV (PLHIV) enrolled in CCLADS and the care providers. Key themes included benefits, limitations, experiences, and perceptions of CCLADS. Benefits to ALHIV included: Longer refills, reduced transport costs, receiving drugs in time, and peer advice; to providers: time-saving, less tiresome, and reduced congestion at the facility. Barriers included: stigma, limited outreaches, and failure to comply. Patients perceived the model positively (cost-effective, improved quality care, no missed appointments), whereas others perceived it negatively (blood samples were not taken like before). Experiences also included enough time, learning some activities, and good adherence. Conclusion: Participation in the CCLADS groups provides several benefits to the patient including reduced transport, longer refills, and good adherence. Stigma remains a challenge to CCLADS participation, which requires innovative and collaborative strategies from the Ministry of Health (MOH) and implementation partners to address to sustain CCLADS participation.